2015
DOI: 10.1186/s13039-015-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variants prioritization after array-CGH analysis – a cohort of 1000 patients

Abstract: BackgroundArray-based comparative genomic hybridization has been assumed to be the first genetic test offered to detect genomic imbalances in patients with unexplained intellectual disability with or without dysmorphisms, multiple congenital anomalies, learning difficulties and autism spectrum disorders.Our study contributes to the genotype/phenotype correlation with the delineation of laboratory criteria which help to classify the different copy number variants (CNVs) detected. We clustered our findings into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 20 publications
4
12
0
9
Order By: Relevance
“…To this end, we considered their size, gene content, inheritance pattern and information from databases and relevant literature [12,14]. Overall, we identified the pathogenic/ likely pathogenic CNVs in 17.7% patients (96/542) which corresponds to the generally held diagnostic yield of 15-20% based on many multicenter studies [20][21][22][23]. Further, 5.9% of all patients had associated karyotypic findings (32/542).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we considered their size, gene content, inheritance pattern and information from databases and relevant literature [12,14]. Overall, we identified the pathogenic/ likely pathogenic CNVs in 17.7% patients (96/542) which corresponds to the generally held diagnostic yield of 15-20% based on many multicenter studies [20][21][22][23]. Further, 5.9% of all patients had associated karyotypic findings (32/542).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of benign CNVs within the genome, the continual discovery of novel CNVs, and the insufficient knowledge of the phenotypic effects of most CNVs have led to the classification of many CNVs as being of unknown clinical significance.Considering that the complex etiology of CLP is not fully understood, the aim of this study was the robust detection of CNVs using a genomic microarray in an attempt to identify chromosomal regions containing causative genes of NSCLP. Although previous studies have reported that common benign CNVs are often smaller in size, with the majority of benign CNVs smaller than 20 kb,14,25,26 here we report small exonic CNVs based on the importance of the affected genes in NSCLP, possibly related to sequence variants in the genes involved in genetic susceptibility to oral clefts.…”
mentioning
confidence: 65%
“…Despite advances in identifying genes associated with the NSCLP development using traditional genetic mapping strategies of candidate genes, genomewide studies, animal models, and epidemiologic and linkage analysis, microarray techniques have become important complementary tools in the search for potential causative CLP genes in genetic studies. These techniques allow investigators to scan the whole genome at once and detect submicroscopic chromosomal imbalances called copy number variants (CNVs) . These genomic imbalances include insertions, duplications, deletions, inversions, recurring mobile elements, and other rearrangements, now usually defined as abnormalities covering 50 or more base pairs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mais recentemente, a tecnologia de aCGH permitiu a descoberta de um grande número de novas síndromes de microdeleção e microduplicação associados a estes distúrbios do desenvolvimento (Shaffer et al, 2007;Slavotinek, 2008). Atualmente, em termos de estratégia de diagnóstico clínico, a técnica de aCGH tem sido considerada como o teste genético de primeira linha para detetar alterações genómicas em doentes com défice intelectual não sindrómico, com ou sem dismorfismos, anomalias congénitas múltiplas, dificuldades de aprendizagem e/ou distúrbios no espectro autista (Carreira et al, 2015;Miller et al, 2010).…”
Section: No âMbito Das Patologias Do Neurodesenvolvimentounclassified